Culturally appropriate nature-based solutions policy settings supporting Indigenous Peoples in Australia—International lessons and applications - Kamaljit K Sangha; Ronju Ahammad; Jeremy Russell-Smith; Marcello Hernández-Blanco; Octavio Pérez-Maqueo; Robert Costanza (Nature-Based Solutions)
Nature-based Solutions (NbS) are fast emerging as action-based approaches to address climate change, biodiversity decline, land degradation, conservation and socio-economic issues. Among a wide range of NbS approaches, Payment for Ecosystem Services (PES) is one of the famous and tried approaches that have been developed and implemented in several countries to date, offering lessons to be learnt for developing innovative NbS-PES ‘systems’ which are beyond the typical market approach and related policy settings, particularly to benefit Indigenous perspectives. To develop such Indigenous-specific PES or more appropriately incentivising schemes for Indigenous Peoples and Local Communities (IPLCs), we analyse and draw lessons from three famous PES schemes from Costa Rica, Mexico, and the Biodiversity Conservation Trust (BCT) from New South Wales (NSW), Australia. We examine their operational policy infrastructure and mechanisms for governing, monitoring, and payments/incentives for Ecosystem Services (ES). One common feature of the selected schemes is the pivotal role of national (Costa Rica and Mexico) and state (NSW) governments in developing specific legislation and regulatory guidelines to mediate these programmes, establish a national/state fund and authority to monitor the contracted conservation sites—offering a standardised and credible arrangement for ES providers and beneficiaries while reducing transactional costs for all parties. Other key learnings include applying a simple, input-based approach and paying land managers on a per-hectare basis for ES as a bundle, using simple indicators such as the state of the forest/ecosystem as a proxy for ES—offering insights for developing nature-based markets for Indigenous peoples in Australia and IPLCs globally. While planning Indigenous-specific schemes, we emphasise that it is critical to consider sociocultural and economic settings in which locals operate to develop equitable and sustainable mechanisms, given that many IPLCs’ value systems are societal and their relationships with nature often lie outside the typical market regimes. Applying IPLCs’ perspectives, we explore a Common Assets Trust model at a state/national scale as an alternative to the market approaches that can afford a common platform for stakeholders to exchange, govern, and monitor ES while also promoting the development of equitable, sustainable, and culturally appropriate incentivizing mechanisms involving low transactional and monitoring costs for IPLCs globally.